Distribution of cave-dwelling phlebotomine sand flies and their nocturnal and diurnal activity in Phitsanulok Province, Thailand - R. Polseela (2018)
An entomological survey of sand flies was conducted in Naresuan Cave in Noen Maprang District, Phitsanulok Province, during November 2009 to December 2010. A total of 10,115 cave-dwelling sand flies were collected with CDC light traps nocturnally (06:00 AM and 06:00 pm) and diurnally (06:00 PM and 06:00 AM). The ratio between male and female sand flies was 1:1.3 (4,363:5,752). The ratio between the number of sand flies caught nocturnally and diurnally was 2.6:1 (7,268:2,847). In this study, 13 species belonging to 4 genera were identified, of which 4 belonged to the genus Phlebotomus, 7 to Sergentomyia, 1 to Nemopalpus and 1 to Chinius. An abundance of species were observed: Nemopalpus vietnamensis (49.15%), P. argentipes (20.15%), C. barbazani (15.79%), P. teshi (9.53%), and S. anodontis (3.21%). Less common species ( < 1%) were S. barraudi (0.63%), P. stantoni (0.57%), S. dentata (0.49%), S.quatei (0.17%), P. philippinensis gouldi (0.12%), S.silvatica (0.10%), S. gemmea (0.05%), and S. iyengari (0.04%). The predominant species in the Naresuan Cave was Nemopalpus vietnamensis (49.15%). The data demonstrates variability in sand fly prevalence, species composition, and relative abundance in caves. P. argentipes was found throughout the day in the caves, which is important because it is believed to be the Leishmania spp vector. This study highlights the diurnal activity of the sand fly and the day-time risk of leishmaniasis. In conclusion, although leishmaniasis has not been reported in Phitsanulok, there should be heightened awareness of infection in these areas with vectors of the protozoa.